Effects of extensive reading on intercultural communicative competence of vietnamese EFL students - Nguyễn Thị Ngọc Vấn (Trường Đại học Trà Vinh, 2022)
For those issues stated, this study aims to explore the effects of extensive reading on Vietnamese EFL students’ intercultural communicative competence in terms of linguistic competence and discourse competence of learners.